Upshots of health education among patients with type 2 diabetes mellitus: A field study in Mysuru - Deepak Anil; D Sunil Kumar; Annaram Ravali; Vijaylakshmi Rao Vadaga; Arun Gopi (Wolters Kluwer Medknow Publications, 2023)
Objective: This study was conducted to assess the impact of health education on lifestyle modification and disease status of diabetic patients for 6 months in rural Mysuru in Southern India. Materials and Methods: A quasi-experimental study was conducted among 104 patients with type 2 diabetes mellitus in rural Mysuru, India from July to December 2022. Participants were assigned to two groups: intervention (n = 52) and control (n = 52), and their data were collected. The intervention group was educated about the disease and its management and was given printed pamphlets containing information to be followed, whereas the participants in the control group were asked to continue their routine health checkups. The body mass index (BMI), weight, fasting blood sugar (FBS), knowledge about the disease, and behavior changes were recorded and compared between the two groups before and after 6 months. Results: The mean FBS value, BMI and weight decreased significantly in the intervention group after 6 months (FBS: 164.79 ± 47.59 mg/dL vs. 141.92 ± 25.63 mg/dL, P < 0.001; BMI: 22.97 ± 3.75 kg/m2 vs. 22.62 ± 3.29 kg/m2, P < 0.05; weight: 62.82 ± 11.92 kg vs. 61.54 ± 10.67 kg, P < 0.05). The posttest period also showed an improvement in physical activity, diet, and medication adherence in the intervention group compared to the control group (P < 0.05). The knowledge scores also improved postintervention which was statistically significant with the Wilcoxon signed-rank test (P < 0.05). Conclusions: The effectiveness of the educational intervention was also supported by lower FBS levels and decrease in BMI and weight compared to before. The findings of this study may help and make it easier to plan studies on people with diabetes mellitus in various settings.